Effectiveness of TKI Inhibitors Combined With PD-1 in Patients With Postoperative Early Recurrence of HCC: A Real-World Study - Li, Zixiong; Han, Ning; Ren, Xueying; Zhang, Yuanjing; Chu, Xiaoyuan (Frontiers in Oncology, 2022)
Objective To observe the efficacy of TKI inhibitor combined with PD-1 treatment in patients with early recurrence after radical resection of HCC, and to analyze the factors that affect the efficacy. Methods The baseline demographic and clinical data of 58 patients with early recurrence after radical resection of HCC (including surgical resection and liver transplantation) were collected. Recurrence and metastasis were classified into early (< or =2 years) and late phase (>2 years). After systemic drug treatment (sorafenib, lenvatinib, PD-1), the efficacy was evaluated based on the RECIST 1.1 standard. COX regression model was used to analyze the factors affecting PFS and OS in HCC patients. Survival curves were drawn by Kaplan-Meier method. Results The study finally included 58 patients who underwent radical resection of HCC, of which 39 were in the TKIs group and 19 were in the TKIs + ICIs combined treatment group. There was no statistical difference in the baseline data of the two groups in HB, PLT, Child-Pugh score and other indicators. Efficacy evaluation results showed that in the 39 TKIs group, 7 patients were PD and 9 patients were PR; while in the 19 TKIs combined with PD-1 group, 2 patients were PD and 6 patients were PR. The median PFS of the TKIs group was 6.2 months, while the median PFS of the TKIs combined PD-1 group was 14.0 months (HR= 0.469, P=0.031). The median OS of the TKIs group was 18.0 months, while the median OS of the TKIs combined with PD-1 group was 35.8 months, an extension of 17.8 months (HR= 0.444, P=0.053). Conclusion In the first-line treatment of patients with early recurrence after radical resection of HCC, patients treated with TKIs combined with PD-1 therapy has a survival advantage over those treated with TKIs alone. Ascites, HBV DNA positivity, and high levels of AFP often indicate poor efficacy of systemic drug therapy, suggesting that such patients should be closely monitored after surgery and that comprehensive systemic treatment should be administrated in time to improve the prognosis.